(untitled) (Research, Society and Development, 2022)
The Clinic in Street Program (CSP) stands out as a comprehensive health care strategy for the Homeless Population, acting in a decentralized, multiprofessional way, within the guidelines of Primary Care. An integrative literature review was carried out with the objective of analyzing the scientific production related to the program from the official documentation to its implementation. In addition, the implementation stage of the program and a cut of its performance in the metropolitan region of São Paulo were verified. The search gathered 16 articles, published between 2013 and 2018, located in the LILACS, SciELO, VHL databases and six official documents involved in the elaboration and implementation of the program found in the official databases of the federal government. Different methodological approaches were adopted in the studies found, with emphasis on observational studies. The inter-ministerial and decentralized management in the development of action strategies was highlighted in the documentation. The evolution of care practices and multidisciplinary work were also highlighted. The program currently has 166 teams, but in the National Registry of Health Establishments (CNES) there is a record of 159 throughout Brazil, 34 in the metropolitan region of São Paulo, which stands out for the number of teams and the implementation of strategies innovative solutions, such as Mobile Dental Units. Which makes us conclude that the PCR is in the process of implementation, with coverage still low in the face of demand, aggravated by the COVID-19 pandemic. highly vulnerable population.